HR 2021
DOI: 10.20517/2394-5079.2021.16
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of C3G and other GEFs to liver cancer development and progression

Abstract: Primary liver cancers constitute the fourth leading cause of cancer mortality worldwide, due to their high morbidity, late diagnosis and lack of effective treatments. Hepatocellular carcinoma (HCC) represents 80% and cholangiocarcinoma (CCA) 15% of liver cancers. Several genetic and epigenetic gene alterations (e.g., TERT, TP53 or CTNNB1) are HCC drivers, although many additional gene alterations contribute to HCC initiation and/or progression. Rho and Ras GTPases have been widely implicated in tumorigenesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 87 publications
(109 reference statements)
1
2
0
Order By: Relevance
“…C3G is expressed in mouse embryonic liver, where an enrichment in shorter isoforms, as compared to brain, was described 22 . We also found that C3G main isoform is expressed in neonatal and adult hepatocytes, as well as in oval cells, but at different levels 23 , 24 . Thus, C3G protein levels are high in both oval cells and neonatal hepatocytes, but low in adult hepatocytes.…”
Section: Introductionsupporting
confidence: 52%
“…C3G is expressed in mouse embryonic liver, where an enrichment in shorter isoforms, as compared to brain, was described 22 . We also found that C3G main isoform is expressed in neonatal and adult hepatocytes, as well as in oval cells, but at different levels 23 , 24 . Thus, C3G protein levels are high in both oval cells and neonatal hepatocytes, but low in adult hepatocytes.…”
Section: Introductionsupporting
confidence: 52%
“…The members of the RASGEFs are SOS, RAPGEF2, RASGRF2, RASGRP1, and RASGRP4. Of these, RASGRP1 was shown to be much more expressed in HCC as compared to the tissues around the tumor, and this high expression was found to be strongly correlated with the size and stage of the tumor (Porras et al 2021). Furthermore, it was discovered by multivariate analysis that RASGRP1 expression constituted a separate risk factor for the advancement of HCC (Porras et al 2021;.…”
Section: Alternate Mechanisms Activating the Mapk Pathway In Hccmentioning
confidence: 99%
“…Of these, RASGRP1 was shown to be much more expressed in HCC as compared to the tissues around the tumor, and this high expression was found to be strongly correlated with the size and stage of the tumor (Porras et al 2021). Furthermore, it was discovered by multivariate analysis that RASGRP1 expression constituted a separate risk factor for the advancement of HCC (Porras et al 2021;. Furthermore, SOS was shown to be a critical molecule implicated in many pathways triggered in HCC, indicating its carcinogenic function in the disease.…”
Section: Alternate Mechanisms Activating the Mapk Pathway In Hccmentioning
confidence: 99%